ENAMEL SURFACE QUALITY IMPROVEMENT IN WHITE SPOT LESIONS AFTER ORTHODONTIC TREATMENT USING A MICROABRASION TECHNIQUE WITH FLUORIDE OR CALCIUM PHOSPHOPEPTIDE-AMORPHOUS CALCIUM PHOSPHATE APPLICATION - Safitri, Novira Mutia; Anggani, Haru Setyo; Purwanegara, Miesje Karmiati; Sumardi, Sariesendy (International Journal of Applied Pharmaceutics, 2018)
Objectives: White spot lesions after fixed orthodontic treatment will increase bacterial plaque formation due to increased enamel surface roughness. The aim of this study was to analyze the surface roughness of white spot lesions on enamel after a microabrasion technique, a microabrasion technique combined with calcium phosphopeptide-amorphous calcium phosphate (CPP-ACP) application, and a microabrasion technique combined with fluoride application. Methods: Artificially induced white spot lesions on the enamel surfaces of 42 maxillary first premolars were randomly assigned into one of three treatment groups (n=14): (a) A microabrasion technique, (b) a microabrasion technique combined with CPP-ACP application, and (c) a microabrasion technique combined with fluoride application. A Mitutoyo SJ-301 surface roughness tester was used to measure differences in surface roughness before and after treatment, and the after treatment measurements were compared among the three groups. Results: A significant difference in surface roughness was noted for the white spot lesions on enamel before and after treatment in all groups (p<0.05). A significant difference was also found when comparing the after treatment surface roughness in all groups. Conclusion: The combination of the microabrasion technique with CPP-ACP application significantly reduced enamel surface roughness when compared to microabrasion alone or the combination of microabrasion and fluoride application.